COMPARATIVE EDUCATIONAL STUDY ON THE EFFICACY OF NORMAL SALINE SOLUTIONS AND SAVLON SALUTIONS IN PERIURETHRA CLEANING TO REDUCE CATHETER-ASSOCIATED BACTERIURIA AT HARAPAN MULIA HOSPITAL IN 2023 - Ximenes, Trinito Abilio; Fauzi, Achmad (HEARTY, 2024)
Background: According to the World Health Organization (WHO) report in 2016, it is stated that in Europe the prevalence of nosocomial infections each year is more than 4 million – 4.5 million patients, while in the United States the prevalence of patients affected by nosocomial infections per year is estimated at around 1,000. 7 million patients. This prevalence represents 4.5% for 99,000 deaths (WHO, 2016). In Indonesia, through the Indonesian Ministry of Health, conducted a survey in 2013 of 10 General Teaching Hospitals, it was found that the number was quite high, 6-16% of nosocomial infections, with an average of 9.8%. A survey conducted in 10 hospitals in DKI Jakarta showed that 9.8% of inpatients received new infections while being treated in hospital (MOH RI, 2013). Research Objectives To determine the description of the frequency distribution of knowledge Nurse hand hygiene as a preventative measure for nosocomial infections in Comparison of the efficacy of normal saline and salvon solutions in cleaning the periurethra to reduce catheter-related bacteriuria in the inpatient room at Harapan Mulia Hospital 2023 Research Methodology: Analytical with a cross sectional approach. The sample in this study was all inpatients who had catheters installed at Harapan Mulia Hospital, totaling 25 people, the sampling technique was total sampling. Research Findings: The results of the analysis show that the majority of respondents who underwent re-hospitalization had good knowledge (100%), but there was no significant relationship with the incidence of re-hospitalization (p-value = 0.09). Likewise, most respondents understood (93.3%), but there was no significant relationship with the incidence of re-hospitalization (p-value = 1.000). In other words, there is no significant relationship between understanding periurethral cleaning and the incidence of re-hospitalization (p-value = 0.09), and there is no significant relationship between understanding nasocomial infections and the incidence of re-hospitalization (p-value = 1,000). Conclusions and Recommendations: The majority of respondents were women (52%), aged 41-50 years (40%), and underwent treatment for 1-3 weeks (80%). However, there was no significant relationship between the efficacy of normal saline against nasocomial infections and the incidence of re-hospitalization in indwelling catheter patients at Harapan Mulia Hospital (p-value > 0.05). Suggestion: increase patient motivation to better understand preventing nasocomial infections to prevent re-hospitalization in patients with indwelling catheters.